Tacit knowledge codification. - A. Jabar, Marzanah; Sidi, Fatimah; Selamat, Mohd Hasan (Science Publications, 2010)
Problem statement: In managing knowledge and competencies as a strategic advantage to an organization, there are difficulties in capturing, storing, sharing and reusing all this knowledge. Researchers have agreed that assessing tacit knowledge is difficult because know how of an employee are elusive and what more to assess them. It is compounded when employees leave the organization or become unavailable due to their mobility within the organization. As a result various approaches to collection and codification of knowledge have emerged. One of the most important approaches to emerge is knowledge management. Approach: In this study, we presented Knowledge Extract, Profiling and Sharing Network (KEPSNet), framework to facilitate the codification knowledge and competencies management adapting knowledge management processes in capturing, storing, sharing and reusing knowledge and competencies. Results: We enhanced these processes autonomously by capturing knowledge and competencies in tacit and explicit form from members of group project implementation in the form of concept maps and managed, according to knowledge management process. A case study in a software development group setting was evaluated and results of knowledge management processes output generated from KEPSNet prototype are compared with the result from the project manager in managing the project based. Two sets of questionnaires were given to the group members before and after implementing KEPSNet. Conclusion/Recommendations: The result of the evaluation validates the viability of the key concept presented. Codification of tacit knowledge has resulted in the codified knowledge and competencies recognized.